Impacto do diagnóstico e tratamento do tumor sobre o consumo de cigarros em pacientes com câncer de cabeça e pescoço - Bugiga, Jéssica Soares [UNESP] (2017)
Maintenance of smoking after diagnosis of head and neck cancer is associated with an increased risk of tumor recurrence and higher mortality rates. To evaluate cigarettes consumption of patients with head and neck cancer at different stages of diagnosis and disease treatment. The study included 46 patients with a diagnosis of squamous cell carcinoma (SCC) of the head and neck who had completed cancer treatment for at least one year. Epidemiological and clinicopathological data were collected from patients' records. A semi-structured questionnaire was used to evaluate cigarette smoking during different stages of cancer treatment. The majority of the patients were men (89%), with tumors located in the mouth (61%), larynx (22%) and oropharynx (17%). Seventeen patients (38%) had clinical stage II and 13 patients (28%) clinical stage IV. After receiving the diagnosis of cancer, 8 patients (18%) ceased smoking, 16 patients (36%) reduced consumption, while 3 patients (7%) increased the intensity of the addiction. After treatment, 11 patients (30%) stopped smoking, 9 patients (25%) decreased consumption of cigarettes and 6 patients (17%) increased consumption. After one year of oncologic treatment, 16 patients (36%) were still smoking, while 28 (64%) did not consume cigarettes any more. The results of the present study indicate that a significant portion of patients with head and neck cancer continue to smoke even after diagnosis and treatment of the disease. Therefore, more specific protocols that evaluate the factors associated with smoking maintenance, as well as their treatment, should be considered in clinical intervention strategies for head and neck cancer